Analisis Hukum Perkawinan Campuran di Indonesia: Tinjauan Yuridis dan Sosio-Kultural - Siarman (Reslaj: Religion Education Social Laa Roiba Journal, 2023)
This study aims to analyze the juridical and socio-cultural aspects of the implementation of mixed marriage laws in Indonesia. Mixed marriages, involving partners from different religious or ethnic backgrounds, have become increasingly common with the rise of mobility and cross-cultural interactions. However, the implementation of laws governing these marriages often encounters various challenges, both administratively and socially. This research employs a qualitative descriptive approach, gathering data through interviews with mixed-marriage couples, civil registration officials, and legal document analysis. The findings reveal that although formal regulations, such as Law No. 1 of 1974 on Marriage, exist, their practical application varies and often poses challenges for mixed-marriage couples. From a socio-cultural perspective, the stigma and social pressure faced by these couples are significantly influenced by cultural and religious backgrounds in different regions. The analysis using progressive legal theory indicates that Indonesian law needs to be more adaptive to serve the needs of an increasingly pluralistic society. The symbolic interaction theory helps explain that the stigma surrounding mixed marriages is constructed through social interactions and can be transformed through public education and inclusive social campaigns. This study concludes that legal reform and enhanced social understanding are necessary to create a more supportive and inclusive environment for mixed-marriage couples in Indonesia.